VIRTUAL AND AUGMENTED REALITY TECHNOLOGIES IN MUSIC CULTURE EDUCATION - Kalonova Farangiz Baxriddinovna, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article explores the use of virtual reality (VR) and augmented reality (AR) technologies in music culture education. It highlights the potential of these immersive technologies to enhance students’ musical perception, engagement, and creativity. The study discusses how VR and AR can provide interactive learning experiences, simulate performance environments, and enable students to explore historical, cultural, and theoretical aspects of music in innovative ways. The article also examines pedagogical strategies for integrating these technologies into music lessons to support competency development and active participation.